2021
DOI: 10.1016/j.spc.2020.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the environmental break-even point for deposit return systems through an LCA analysis of single-use and reusable cups

Abstract: Assessment of the environmental break-even point for deposit return systems through an LCA analysis of single-use and reusable cups Journal Pre-proof Assessment of the environmental break-even point for deposit return systems through an LCA analysis of single-use and reusable cups

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…This environmental breakeven point for reusable cups is dependent on washing location and transportation distance. In this study both PP and PET showed the best environmental performance 22 …”
Section: Resultsmentioning
confidence: 52%
See 2 more Smart Citations
“…This environmental breakeven point for reusable cups is dependent on washing location and transportation distance. In this study both PP and PET showed the best environmental performance 22 …”
Section: Resultsmentioning
confidence: 52%
“…Furthermore, it is notable that the energy cost per package as well as the carbon footprint has continued in a favorable reduction of 50% over the last decade with it possible for industry to produce more than 150 0.5 L bottles with 1 kg of PET where in 2010 70 to 80 was typical 1,2 . While the studies referenced here are recent, PET was generally analyzed at container weights that are historically heavy or otherwise leave room for improvement, meaning the analysis was a conservative under prediction, whether of single‐use cup performance, 22 or the various bottle studies. Lightweighting has less room for improvement in aluminum or glass.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This means some consumers might be inaccurately thinking they are making the most sustainable choices when another alternative is environmentally preferable. Currently, there are many LCA studies on everyday consumer products such as plastic carrier bags (Edwards, 1998;Greene, 2011;Kimmel et al, 2014;Bisinella, 2018), disposable cups (Openbare, 2006;Ligthart & Ansems , 2007;Van der Harst & Potting, 2013, Cottafava, D. et al, 2020, plates (Postacchini et al, 2016), milk bottles (Keoleian & Spitzley, 1999), take-away containers (Madival, S. et al, 2009;Accorsi et al, 2014;Bortolini, M. et al, 2018;Gallego-Schmidt et al, 2019) and other food packaging options (Franklin Associates, 2018). These papers demonstrate the complexity of product sustainability, the nuances of the environmental impact of reusable items, and the number of factors and behaviors results are dependent on.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of authors agree that reuse of packaging has a huge potential for environmental impact reduction through the decreased need of materials, especially virgin or primary materials, when the reuse systems are well developed and function sustainably [17,24].…”
Section: Introductionmentioning
confidence: 99%